Natural coumarins: Preclinical evidence-based potential candidates to alleviate diabetic nephropathy - Sitara Ghosh; Ankana Ghosh; Ashitha Rajanan; Amal Jyothy Suresh; Pratiksha Sharadrao Raut; Sourav Kundu; Bidya Dhar Sahu (Elsevier, 2022)
Background: Cis-o-hydroxycinnamic acid lactones, referred to as natural coumarin, have a basic skeleton of benzopyranone in their structure. The natural coumarins are typically found abundantly in roots, rhizomes, bark, and leaves of the plant belonging to the families of Apiaceae, Rutaceae, Lamiaceae, Asteraceae, Oleaceae, and Thymelaeaceae. A few familiar food sources containing coumarin include citrus fruits, carrots, apricot, cherries, strawberries, cinnamon, parsnip, and fennels. Coumarins are attracting much attention and are becoming a tremendously appealing topic because of their potent pharmacological actions modulating through various signaling mechanisms. Purpose: The present review closely inspects the protective actions of natural coumarins like osthole, umbelliferone, esculin, daphnetin, urolithins, esculetin, psoralen, scopoletin, nodakenin, and imperatorin against diabetic nephropathy and the underlying cellular and molecular mechanisms. Methods: Using Science Direct, PubMed, Google Scholar, and Scopus, we performed a comprehensive literature search of published papers by using the keywords "osthole and diabetic nephropathy" or "umbelliferone and diabetic nephropathy" or "esculin and diabetic nephropathy" or "daphnetin and diabetic nephropathy" or "urolithins and diabetic nephropathy" or "esculetin and diabetic nephropathy" or "psoralen and diabetic nephropathy" or "scopoletin and diabetic nephropathy" or "nodakenin and diabetic nephropathy" and "imperatorin and diabetic nephropathy". Results: Studies show that these selected coumarins have potent anti-inflammatory and antioxidant properties, showing protective action against diabetic nephropathy. These coumarins reduce the levels of reactive oxygen species and lipid peroxidation, formation of advanced glycation end products (AGEs), perturbation of pro-inflammatory cytokines, and activation of cellular pathways, including TGF-β/Smad, NF-kB (p65), and NLRP3/Caspase 1 axis. Accumulating evidence also suggests coumarins interfere with the activation of α-smooth muscle action (α-SMA) secreting myofibroblasts, synthesis, and accumulation of extracellular matrix (ECM) components in the kidneys. Conclusion: Nephropathy is an important complication of diabetes mellitus which accelerates the progression to end-stage renal disease. Our findings suggest that these natural coumarins have the potential for diabetic nephropathy and therapy. Nevertheless, these natural coumarins must be confirmed for their toxicity, bioavailability, and formulation aspects for further development.